Thinking out of the box?What teachers must do to foster higher order thinking skills in accounting graduates. - Lau, Adeline H P (Universiti Sains Malaysia, 2008)

(untitled)
This paper addresses the concern that accounting education is inadequate in equipping accounting graduates for the challenges of today' s workforce. The study posits that students need to be taught higher-order thinking skills and to engage in deep learning in order to succeed in today's workplace. The underlying belief is deep learning is hard work and unless students are taught critical thinking skills, they cannot initiate deep learning, let alone sustain the effort.